ANALISIS FAKTOR-FAKTOR PENDUKUNG DAN KUALITAS INFORMASI PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH KEUANGAN PADA PEMERINTAH KOTA KENDARI - Ramesa, Haryati Saleh (JURNAL AKUNTANSI, 2016)
This study aims to know the factors supporting owned of Agency of finance and assets management area (BPKAD) Kendari so as to apply early finance SIMDA, as well as the quality of the information generated from the implementation of finance SIMDA. Responden in the study as much as 5 (five) people consisting of BPKAD Kendari is officer in the administration, officer in the budgeting, officer in the accounting and reporting, administrator of finance SIMDA and head of BPKAD Kendari. Data were collated through direct interviews with the responden using an interview guide, direct observation of the activities of employees BPKPD Kendari and documentation study of related documents. The interviews and data collected were analyzed by using descriptive method.Results from the study showed that in general employees BPKAD Kendari already have the factors to support the implementation of finance SIMDA, namely : communication, human resources, the attitude/disposition and bureaucratic structure. While the quality of the information generated from the implementation of finance SIMDA, namely timeliness, accuracy, and relevant. Key words : finance SIMDA, supporting factors, quality of information